Analisis Komparatif Modus Operandi dan Kerentanan Sistem dalam Kasus Korupsi di Sektor Keuangan dan BUMN - Tasya Nurhalyz; Nelya Arofatin; Yaohan Ad’nnia Jannah; Tries Ellia Sandari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines cases of corruption in Indonesia’s financial sector and state-owned enterprises (SOEs), focusing on PT A, PT B, and PT C. The research aims to analyze and compare the modus operandi and system vulnerabilities that enable corruption in these companies. Data were collected through analysis of investigation and financial audit reports, legal literature, and relevant regulations, specifically the Anti-Corruption Law (UU TIPIKOR) and the Anti-Money Laundering Law (UU TPPU). Findings reveal that weak internal controls and limited forensic accounting practices are key factors facilitating corruption, including embezzlement at PT A, procurement specification manipulation at PT B, and fictitious transactions at PT C. The application of forensic accounting and strengthening of internal control systems are essential in detecting and preventing financial manipulation, which can be detrimental to the state. This study recommends implementing forensic accounting, reinforcing internal oversight, conducting stricter procurement audits, and fostering interagency cooperation to enhance effective anti-corruption measures.